Haplotype‐based association of Vascular Endothelial Growth Factor gene polymorphisms with urothelial bladder cancer risk in Tunisian population. Issue 9 (29th June 2018) - Ben Wafi, Safa; Kallel, Amani; Ben Fradj, Mohamed Kacem; Sallemi, Ahmed; Ben Rhouma, Sami; Ben Halima, Meriam; Sanhaji, Haifa; Nouira, Yassine; Jemaa, Riadh; Feki, Moncef
Abstract : Background/Aim: Accumulated data suggested that Vascular Endothelial Growth Factor is a major mediator in vasculogenesis, angiogenesis and recently in tumorigenesis. Therefore, we aimed to investigate for the first time the association between VEGF gene variants (‐2549I/D (rs35569394), ‐2578C/A (rs699947), and +936C/T (rs3025039)) with urothelial bladder cancer (UBC) in Tunisian population. Methods: A total of 218 UBC patients and 204 controls were recruited and genotyped by Polymerase Chain Reaction technique. Odds ratios (OR) and 95% confidence intervals (CIs) were used to access the association between the VEGFA gene polymorphisms and UBC. Results: We found a significant decreased risk association of ‐2578 C/A polymorphism with UBC (OR (95% CI), 0.62 (0.41‐0.94), P = .026) for CA genotype and (OR (95% CI), 0.40 (0.21‐0.76), P = .005) for double homozygous mutant genotype. No associations were found in case of both polymorphic sites of VEGF, vis. ‐2549I/D and +936C/T, respectively. Haplotype analysis revealed a strong linkage disequilibrium between ‐2578C/A and ‐2549I/D and CIC combination is the significant haplotype associated with increased risk of UBC (OR (95% CI), 3.63 (1.47‐8.97), P = .005). Regarding tumor grade/stage and family history of cancer, no associations were found for ‐2578C/A polymorphism. Conclusion: CIC haplotype of VEGF gene may be important risk factor for UBC development in Tunisia.